2016
DOI: 10.1186/s40199-016-0148-7
|View full text |Cite
|
Sign up to set email alerts
|

A model for priority setting of health technology assessment: the experience of AHP-TOPSIS combination approach

Abstract: BackgroundIn recent times, the use of health technologies in the diagnosis and treatment of diseases experienced considerable and accelerated growth. The goal of the present study was to describe the designated pilot MCDM (Multiple Criteria Decision Making) model for priority setting of health technology assessment in Iran.MethodsRelevant articles were sought and retrieved from the most appropriate medical databases, including the Cochrane Library, PubMed and Scopus via three separate search strategies, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 19 publications
1
28
0
2
Order By: Relevance
“…The maintenance and likely costs, which have a negative nature, are the criteria that obtained the highest values for the vector weight, and for both of them, the monopile has a much lower score than the jacket; hence, it can be concluded that the effect of these extreme scores has been underestimated by using these less sophisticated methods. Results obtained from the deterministic application of the different methods employed in this paper can be supported by the findings of other studies for similar problems comparing different MCDM methods, i.e., [82][83][84].…”
Section: Deterministic Resultssupporting
confidence: 85%
“…The maintenance and likely costs, which have a negative nature, are the criteria that obtained the highest values for the vector weight, and for both of them, the monopile has a much lower score than the jacket; hence, it can be concluded that the effect of these extreme scores has been underestimated by using these less sophisticated methods. Results obtained from the deterministic application of the different methods employed in this paper can be supported by the findings of other studies for similar problems comparing different MCDM methods, i.e., [82][83][84].…”
Section: Deterministic Resultssupporting
confidence: 85%
“…For this, the information is structured according to the following fields: names of the authors, title of the article, methodologies (HTA or mini-HTA or any other unspecified methodology), multi-criteria techniques and main assessment criteria (health problems and use of technology, description and technical characteristics, safety, clinical effectiveness, costs and economic evaluation, ethical analysis, organizational / institutional aspects and human resources, patient and social aspects, legal aspects, among others). In addition, 14 guidelines and methodologies proposed by international HTA agencies were reviewed, allowing the conceptualization of methodologies used internationally [11,12,16,23,24,30,31,[33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Methodsmentioning
confidence: 99%
“…Sequentially, the multi-criteria decision tool from AHP was selected, which is widely used in different areas, such as: health, political, economic, social and management sciences [20][21][22][23][24][25][26]. One of the relevant characteristics for the selection of this tool was its natural capacity to perform bi-univocal comparisons through matrix operations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta equaçaõ deriva a prioridade dos elementos, sendo mais adequada para certas decisões em grupo (Dong et al, 2010). Após o cálculo da media geometrica dos elementos de cada linha, o vetor obtido é normalizado para obter o vetor prioridade (Mobinizadeh et al 2016).…”
Section: Metodologia De Pesquisaunclassified